Staging of tau distribution by positron emission tomography may be useful in clinical staging of Alzheimer disease. Issue 2 (9th January 2020) - Aohara, Kenta; Minatani, Shinobu; Kimura, Hiroko; Takeuchi, Jun; Takeda, Akitoshi; Kawabe, Joji; Wada, Yasuhiro; Mawatari, Aya; Watanabe, Yasuyoshi; Shimada, Hitoshi; Higuchi, Makoto; Suhara, Tetsuya; et al.
Abstract: Background: Clinical staging of Alzheimer disease (AD) may help develop novel treatment in the early stage. Aim: We measured the accumulation of amyloid beta (Aβ) and tau with positron emission tomography (PET) in patients with AD to explore its utility for clinical staging. Methods: Six patients with AD, two patients with mild cognitive impairment (MCI), and 12 healthy controls (HC) were studied. Aβ and tau accumulation was evaluated with [ 11 C]PiB and [ 11 C]PBB3, respectively. Results: PBB3‐PET showed that two cases were in stage I‐II (Braak stage), one case was in stage III‐IV, and three cases were in stage V‐VI. PiB‐PET showed that all cases were in stage C. The duration of the disease correlated positively with PBB3 staging but not with PiB staging. The performance on the Mini‐Mental State Examination (MMSE) tended to decrease with advancing of PBB3 stage but not with PiB stage. PBB3 SUVR and PiB SUVR in all AD signature areas including the parahippocampal gyrus were significantly higher in AD than in HC. A decrease in MMSE is correlated with increases in PBB3 and PiB. Increase in PBB3 started with decrease in MMSE whereas increase in PiB was already observed in the point of highest MMSE, indicating amyloid is already accumulated in the earliest stage. Conclusions: The expansion of tau distribution from the parahippocampal gyrus to the cerebral cortex was observed with advancing AD, whereas Aβ distribution was already advanced in the earliest stage. PBB3 may be useful in determining stages in AD based on tau distribution.